Efficient energy localization for hybrid wideband hyperthermia treatment system. Issue 3 (12th January 2018) - Uddin, Nizam; Elshafiey, Ibrahim
Abstract: This article presents efficient energy localization approach for hybrid wideband system for hyperthermia treatment of cancer based on a transmission line (TL). A heterogeneous head phantom is built by incorporating frequency dependent tissue properties of head layers considering both electromagnetic and ultrasound treatment. Effective medium properties are derived and used to compensate signal phase and magnitude values based on TL model. The obtained field map results emphasize the feasibility of the developed approach to obtain system parameters that enhance energy localization and eradicate hotspots.